Avtorskopravne podlage za grajenje velikih jezikovnih modelov v slovenski pravni ureditvi - Bogataj Jančič, Maja (Pravni letopis, 2025)
Legal certainty and the efficiency of copyright regulation are key to building large language models that depend on processing large amounts of text and data. Slovenian copyright legislation has two new exceptions related to data analysis or text and data mining, which also constitute the legal basis for building generative artificial intelligence, including large language models. The exceptions were introduced into Slovenian copyright legislation with the latest amendment to the Copyright and Related Rights Act (ZASP-I) in October 2022, with which Slovenia implemented the provisions of Directive (EU) 2019/790 on copyright and related rights in the Digital Single Market into its national legal order. The article presents solutions for how other jurisdictions around the world have dealt with the issue of providing copyright legal basis for building large language models. The main part of the article focuses on the interpretation of the Slovenian exception for text and data mining for the purposes of scientific research, which is the key legal basis for building an open-source large language model for the Slovenian language. The conclusion sheds light on the dilemmas currently facing the EU, which is otherwise making huge investments in building artificial intelligence in the public interest (Public AI), such as the construction of an open-source large language model for the Slovenian language and indicates possible directions for development.
Keywords: avtorsko pravo; avtorskopravne izjeme za besedilno in podatkovno rudarjenje; copyright exceptions for text and data mining; copyright law; generative artificial intelligence; generativna umetna inteligenca; large language models; lawful access; veliki jezikovni modeli; zakoniti dostop